2015
DOI: 10.1089/cap.2014.0178
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Dopamine Beta Hydroxylase Gene Moderate Atomoxetine Response in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Objective: Atomoxetine is the most widely used nonstimulant for the treatment of attention-deficit/hyperactivity disorder (ADHD). It selectively acts on the norepinephrine (NE) system. Dopamine beta hydroxylase (DBH) regulates the synthesis of NE. This study aimed to investigate whether variants in the DBH gene have an effect on the differential response to atomoxetine. Methods: Children and adolescents with ADHD were enrolled in a prospective, open-label study of atomoxetine for 8-12 weeks. The dose was titra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This finding was also observed in a meta‐analysis by Catalá‐López, that found a significant adverse health and longevity effect in both autism spectrum disorder and ADHD (Catala‐Lopez et al ). DβH has been widely implicated in ADHD with increased risk, reduced life, and altered pharmacological efficacy (Fang et al ; Tong et al ; Barkley et al ). A longitudinal study performed by Barkley et al () found that the DβH Taq1 A1 and A2 gene polymorphisms contribute to lower estimated life expectancy in ADHD patients.…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was also observed in a meta‐analysis by Catalá‐López, that found a significant adverse health and longevity effect in both autism spectrum disorder and ADHD (Catala‐Lopez et al ). DβH has been widely implicated in ADHD with increased risk, reduced life, and altered pharmacological efficacy (Fang et al ; Tong et al ; Barkley et al ). A longitudinal study performed by Barkley et al () found that the DβH Taq1 A1 and A2 gene polymorphisms contribute to lower estimated life expectancy in ADHD patients.…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
“…Their in vitro gene expression studies showed that cells that are homozygous for the rs129882 variant produce a 2‐fold decrease in luciferase activity. Another study in ADHD reports that rs2519154 (located in intron five) is highly correlated with altered pharmacological intervention in children and adolescents (Fang et al ). Patients carrying either the heterozygous or homozygous rs2519154 polymorphism had a better response to atomoxetine, a mainline medication for ADHD treatment, compared to wild‐type (Fang et al ).…”
Section: Neuropsychiatric Issues and Dβhmentioning
confidence: 99%
See 1 more Smart Citation
“…Four SNPs in the dopamine β-hydroxylase gene (DBH) were found nominally associated with atomoxetine response status in a Chinese sample of 153 children and adolescents with ADHD (rs1076150, rs2873804, rs1548364, and rs2519154). The association between rs2519154 and atomoxetine response remained significant after correction for multiple comparisons (Fang et al, 2015). Ramoz et al (2009) also investigated atomoxetine response in association with SLC6A2 and CYP2D6 gene SNPs.…”
Section: Genetic Markers For Treatment Responsementioning
confidence: 99%
“…The DBH gene polymorphism (C-1021T) has been reported to moderate treatment outcome with several medications in patients with various medical and psychiatric conditions including CUD (Fang et al, 2015;Kosten et al, 2013;Liu et al, 2014;Schottenfeld et al, 2014). Here, we report greater efficacy of doxazosin (8 mg/day) in reducing cocaine use in individuals with the DBH C-1021T CT or TT genotype (low DβH and NE levels) than those with the CC genotype.…”
Section: Discussionmentioning
confidence: 61%